Ethical Challenges in Advanced Medicine - Anna Meyfour; Alireza Nikoofar; Masoud Nakhaei Moghadam (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Medical ethics is an interdisciplinary science about matters and ethical issues in the field of medical. In the twentieth century, scientific advances earn more success in the field of medicine. This development creates problems and questions that profound changes in medical ethics are required to answers them. Today, discussions of important issues in biotechnology field have attracted the attention of moral philosophers. The issues that the modern medical ethics try to resolve them are included professional Communications in medicine, law and the role of the patient in treatment, organs and tissues transplantation, euthanasia, Abortion, Simulation and new methods of contraception and   Pregnancy induction . In this article, we tried to discuss about these important issues. Keywords: Medical ethics; Euthanasia; Abortion; Organ transplantation For downloading the full-text of this article please click here.